Effectiveness of Using Local Languages in Education to Improve Knowledge about Foot Care in Diabetes Mellitus Patients - Eva Arna Abrar; Fitri A. Sabil; Syaiful Syaiful; Sintawati Sintawati (Sarana Ilmu Indonesia (salnesia), 2022)
Diabetes mellitus (DM) still has the highest number to date with increasingly diverse complications, one of which is diabetic foot ulcers (DFU). One of the efforts to prevent DFU is to provide education to patients to increase knowledge in performing foot care. In providing education, the use of local languages ??that are easily understood by patients will have a good impact on the process of receiving information. This study aimed to analyze the patient's knowledge in performing foot care before and after providing foot care education using the local language. Research design one group pre-post test was conducted in one of the Makassar City health centers with a total of 47 subjects. Knowledge measurement was carried out before giving education and evaluation was carried out after four weeks. Patients were given foot care packages that are in accordance with the contents of the educational video. The results of statistical tests showed that there was a significant improvement in knowledge of foot care before and after education with a p value = 0,000. Education using local languages ??could significantly increase knowledge of foot care in DM patients.